bHLH heterodimer complex variations regulate cell proliferation activity in the meristems of Arabidopsis thaliana - Mor, Eliana; Pernisová, Markéta; Minne, Max; Cerutti, Guillaume; Ripper, Dagmar; Nolf, Jonah; Andres, Jennifer; Ragni, Laura; Zurbriggen, Matias D; De Rybel, Bert; Vernoux, Teva (iScience, 2022)
Root, shoot, and lateral meristems are the main regions of cell proliferation in plants. It has been proposed that meristems might have evolved dedicated transcriptional networks to balance cell proliferation. Here, we show that basic helix-loop-helix (bHLH) transcription factor heterodimers formed by members of the TARGET OF MONOPTEROS5 (TMO5) and LONESOME HIGHWAY (LHW) subclades are general regulators of cell proliferation in all meristems. Yet, genetics and expression analyses suggest specific functions of these transcription factors in distinct meristems, possibly due to their expression domains determining heterodimer complex variations within meristems, and to a certain extent to the absence of some of them in a given meristem. Target gene specificity analysis for heterodimer complexes focusing on the LONELY GUY gene targets further suggests differences in transcriptional responses through heterodimer diversification that could allow a common bHLH heterodimer complex module to contribute to cell proliferation control in multiple meristems.
Keywords: Natural sciences; Molecular plant pathology; Plant biology; Biological sciences